PENGAMANAN PESAN STEGANOGRAFI DENGAN METODE LSB BERLAPIS ENKRIPSI - Widyawan, Tri Ismardiko (JIK: Jurnal Ilmu Komputer, 2018)
Security in communication is a top priority in the use of steganography. This concept allows us to convey messages to people we want through a media without arousing suspicion to others. In this case the media used is digital media. More specifically digital media used are image media because images are the most popular media in secret message hiding. The increasingly widespread use of the internet as a communication medium is the reason why this message insertion technique uses the PHP programming language that is currently popular as a programming language supporting web-based applications. The LSB (Least Significant Byte) method is a message hiding technique in steganography where the hidden message is hidden by replacing the data bits in the image segment with secret message bits. Secret message bits are inserted in the low bit or the rightmost bit in the pixel composing the image consisting of red, green and blue (RGB), each of which has an 8-bit value of 0 to 255 with binary format 00000000 to 11111111. Thus, 3 bits of data can be inserted in each pixel image available. The LSB method is then applied in a library which is then named as a stegger which has the function to insert messages in images using the PHP programming language. To add protection to messages sent, an encryption algorithm is added that has been arranged in a class named secrypt that is accompanied by keyword inclusion so that the message sent has a higher level of security.Ã‚Â Keywords: steganography, PHP, encryption, stegger, secrypt